PENGALAMAN PASIEN SUKU BATAK KARO DENGAN GAGAL GINJAL KRONIS DALAM MENJALANI HEMODIALISA - Lenny Lusia Simatupang (Indonesian Trust Health Journal, 2018)
The experience of patients undergoing hemodialysis therapy is a phenomenon and attracts the attention of health professionals, because in Hemodialysis (HD) therapy, participants leave a number of important issues, as a result of hemodialysis therapy. The purpose of this study to determine the experience of Karo Batak patients with Chronic Kidney Failure (GGK) in undergoing hemodialysis. This study is a descriptive phenomenology study. Data collection was done by indepth interview. Participants in this study amounted to 13 people selected by purposive sampling technique of participants who have a Batak Karo tribe and duration of hemodialysis for at least six months. Conducting interviews conducted in hospital Murni Teguh, contract researcher with participants and researchers conducted interviews .. The results of interviews were analyzed by collaizi method and found 3 themes in the results of interviews with the participants.Themes encountered are mood and mind hemodialisa patient, Helplessness to meet the needs live, Following the traditional medicine Batak karo. Based on the results of the study, it is suggested to the nurse in providing hemodialysis treatment to pay attention to traditional medicine which is also used by the patient so that it can reduce the problem of patients undergoing hemodialysis. Abstrak Pengalaman pasien yang menjalani terapi hemodialisa sangat fenomena dan menarik perhatian para professional kesehatan, karena didalam menjalani terapi Hemodialisis (HD), partisipan menyisakan sejumlah persoalan penting, sebagai dampak terapi hemodialisa. Tujuan dari penelitian ini untuk mengetahui pengalaman pasien suku Batak Karo dengan Gagal Ginjal Kronis (GGK) dalam menjalani hemodialisa. Penelitian ini merupakan studi fenomenologi deskriptif. Pengumpulan data dilakukan dengan indepth interview. Partisipan dalam penelitian ini berjumlah 13 orang yang dipilih dengan teknik purpossive sampling partisipan yang bersuku Batak Karo dan lamanya menjalani hemodialisa minimal enam bulan. Pelaksanaan wawancara dilakukan di rumah sakit Murni Teguh, peneliti kontrak dengan partisipan dan peneliti melakukan wawancara.. Hasil wawancara dianalisa dengan metode collaizi dan ditemukan 3 tema pada hasil wawancara dengan para partisipan.Tema yang dijumpai yaitu Suasana hati dan pikiran pasien hemodialisa, Ketidakberdayaan memenuhi kebutuhan hidup, Mengikuti pengobatan tradisional Batak karo. Berdasarkan hasil penelitian, disarankan kepada perawat dalam memberikan perawatan hemodialisa memperhatikan pengobatan tradisional yang juga digunakan oleh pasien sehingga bisa mengurangi masalah pasien yang menjalani hemodialisa.